2000
DOI: 10.1007/bf02256912
|View full text |Cite
|
Sign up to set email alerts
|

IR spectra of 2-alkylamino-and alkylnitramino-3-or 5-nitro-4-methylpyridine derivatives

Abstract: This paper is a part of our systematic spectroscopic investigations on alkylamino-and alkylnitramino-3-or 5-nitropicolines [1][2][3][4]. It is interesting how the presence of three substituents of different electronic properties influence the spectra of the studied compounds. EXPERIMENTALThe synthesis of the investigated compounds has been described in a previous publication [5]. IR spectra were recorded on a Specord LR-80 (Zeiss, Jena) spcctrophotometer as nujol mulls. RESULTS AND DISCUSSIONInfrared spectra o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…3A) at this frequency is most likely due to the asymmetric NO 2 stretch of nitro compounds. 55,56 The formation of nitrocontaining organics is likely due to addition of NO 2 to the alkyl radical formed upon addition of NO 3 to the double bond. 1 Other mode assignments were aided by the creation of a reference sample composed of a thin film of 2-ethylhexyl nitrate (C 4 H 9 CH(C 2 H 6 )CH 2 ONO 2 ) on gold.…”
Section: Ir Characterization Of H 2 Cq Q Qch-sams During No 3 Exposurementioning
confidence: 99%
“…3A) at this frequency is most likely due to the asymmetric NO 2 stretch of nitro compounds. 55,56 The formation of nitrocontaining organics is likely due to addition of NO 2 to the alkyl radical formed upon addition of NO 3 to the double bond. 1 Other mode assignments were aided by the creation of a reference sample composed of a thin film of 2-ethylhexyl nitrate (C 4 H 9 CH(C 2 H 6 )CH 2 ONO 2 ) on gold.…”
Section: Ir Characterization Of H 2 Cq Q Qch-sams During No 3 Exposurementioning
confidence: 99%
“…The chemical shifts of H-6 (δ H 8.75), H-8 (δ H 8.14), and C-7 (δ C 148.9) suggested the presence of a functionality with strong electron-withdrawing effects, such as a NO 2 group, at C-7. The NO 2 functionality was supported by characteristic IR absorptions at 1527 and 1349 cm −1 …”
Section: Resultsmentioning
confidence: 97%
“…The NO 2 functionality was supported by characteristic IR absorptions at 1527 and 1349 cm -1 . 14 Substructure B (B, Figure 1) was assembled starting with the N-methyl resonance that showed HMBC correlations to carbons C-1 (δ C 165.5) and C-3 (δ C 76.7). The H 2 -3a methylene signal (δ H 4.34 and 4.52) showed HMBC correlations with C-3 (δ C 76.7) and C-4 (δ C 161.4).…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H and 13 C NMR spectroscopic data of 1 were very similar to those of glionitrin A ( 2 ), with the exception of two S -methyl signals (δ H 2.36 and δ C 12.2 vs δ H 2.27 and δ C 13.2). The 13 C chemical shift of C-7 (δ C 148.0) and the IR absorption bands at 1526 and 1347 cm –1 indicated that glionitrin B ( 1 ) contained a nitro functionality. The substituted positions of the two S -methyl groups were determined as C-3 and C-10a on the basis of the key HMBC correlations from a S -methyl proton at δ H 2.36 to a quaternary carbon at δ C 72.4 and from a S -methyl proton at δ H 2.27 to a quaternary carbon at δ C 71.8 (see Figure S1 thru S14 in the Supporting Information for the spectral data of 1 ).…”
mentioning
confidence: 99%